The Influence of Parents' Income and Learning Motivation on Interest in Continuing Study at Higher Education in Accounting Class XII Students at Prayatna 1 Vocational High School Medan, Academic Year 2021/2022 - Tuti Sriwedari (Outline Publisher, 2023)
The purpose of this study was to determine the effect of active learning and the role of parents in online learning on the learning outcomes of class X students in Office Administration SMK PAB 2 Helvetia. the sample used was 57 students taken randomly from 133 students. The results obtained are that there is an influence between learning activity and the role of parents in online learning on the learning outcomes of class X students of Office Administration SMK PAB 2 Helvetia, either partially or simultaneously.